1997
DOI: 10.1108/00070709710169067
|View full text |Cite
|
Sign up to set email alerts
|

An exploratory study into the adoption of capital budgeting techniques by agricultural co‐operatives

Abstract: Finds that agricultural co-operatives have not been as sophisticated in their utilization of capital budgeting as a planning and financial management tool as have traditional corporations. Suggests that this may be due to the differences in the organizational objectives of the co-operatives and the forprofit corporations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0
1

Year Published

1997
1997
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 11 publications
0
5
0
1
Order By: Relevance
“…With regard to practices for investment analysis found in the studies, the Payback Period is noticed as the most used (Block, 2003;Brijlal & Quesada, 2009;Brounen et al, 2004;Holmén & Pramborg, 2009;Kwong, 1986;Lam et al, 2007;Lazaridis, 2004;Peel & Bridge, 1998Pike, 1982Pike, , 1985Pike, , 1988Sandahl & Sjogren, 2003;Schall, Sundem & Geijsbeek, 1978;White, Miles & Munilla, 1997).…”
Section: Studies On Capital Budgeting Practicesmentioning
confidence: 99%
“…With regard to practices for investment analysis found in the studies, the Payback Period is noticed as the most used (Block, 2003;Brijlal & Quesada, 2009;Brounen et al, 2004;Holmén & Pramborg, 2009;Kwong, 1986;Lam et al, 2007;Lazaridis, 2004;Peel & Bridge, 1998Pike, 1982Pike, , 1985Pike, , 1988Sandahl & Sjogren, 2003;Schall, Sundem & Geijsbeek, 1978;White, Miles & Munilla, 1997).…”
Section: Studies On Capital Budgeting Practicesmentioning
confidence: 99%
“…This argument is supported by the findings of some studies, such as Kamath and Elmer (1989) and Kamath and Oberst (1992), that smaller percentage of hospitals, as not-for-profit units, account for risk in their capital budgeting decisions than their profitmaking counterparts. And as stated before, White et al (1997) attribute the lack of formal treatment of risk in not-for-profit organizations to the difficulties encountered in explicit incorporation of risk in the capital investment evaluation. Thus, hypothesis six can be stated as follows:…”
Section: Attitude Towards Riskmentioning
confidence: 93%
“…As mentioned earlier, recent research has shown that there is an increased awareness of the discounted cash flow techniques in private and governmental or nonprofit organization (Pike, 1988;White et al, 1997;Bailes et al, 1998;and Sekwat, 1999). Specifically, Sekwat (1999) shows that capital budgeting is regarded as efficiency improving tool in local governments (municipalities) in part of the U.S.…”
Section: Adoption Of Capital Budgeting Techniquesmentioning
confidence: 95%
See 2 more Smart Citations